Intravenous Thrombolysis in Unknown-Onset Stroke: Results From the Safe Implementation of Treatment in Stroke-International Stroke Thrombolysis Registry - Dorado, Laura; Ahmed, Niaz; Thomalla, Götz; Lozano, Manuel; Malojcic, Branko; Wani, Mushtaq; Millán, Mònica; Tomek, Ales; Dávalos, Antoni (Stroke, 2017)
BACKGROUND AND PURPOSE: Stroke patients with unknown onset (UKO) are excluded from thrombolytic therapy. We aim to study the safety and efficacy of intravenous alteplase in ischemic stroke patients with UKO of symptoms compared with those treated within 4.5 hours in a large cohort. METHODS: Data were analyzed from 47 237 patients with acute ischemic stroke receiving intravenous tissue-type plasminogen activator in hospitals participating in the Safe Implementation of Treatment in Stroke-International Stroke Thrombolysis Registry between 2010 and 2014. Two groups were defined: (1) patients with UKO (n=502) and (2) patients treated within 4.5 hours of stroke onset (n=44 875). Outcome measures were symptomatic intracerebral hemorrhage per Safe Implementation of Treatment in Stroke on the 22 to 36 hours post-treatment neuroimaging and mortality and functional outcome assessed by the modified Rankin Scale at 3 months. RESULTS: Patients in UKO group were significantly older, had more severe stroke at baseline, and longer door-to-needle times than patients in the ≤4.5 hours group. Logistic regression showed similar risk of symptomatic intracerebral hemorrhage (adjusted odds ratio, 1.09; 95% confidence interval, 0.44-2.67) and no significant differences in functional independency (modified Rankin Scale score of 0-2; adjusted odds ratio, 0.79; 95% confidence interval, 0.56-1.10), but higher mortality (adjusted odds ratio, 1.58; 95% confidence interval, 1.04-2.41) in the UKO group compared with the ≤4.5 hours group. Patients treated within 4.5 hours showed reduced disability over the entire range of modified Rankin Scale compared with the UKO group (common adjusted odds ratio, 1.29; 95% confidence interval, 1.01-1.65). CONCLUSIONS: Our data suggest no excess risk of symptomatic intracerebral hemorrhage but increased mortality and reduced favorable outcome in patients with UKO stroke compared with patients treated within the approved time window.
Keywords: Tissue Plasminogen Activator; stroke; Aged; cerebral hemorrhage; Thrombolytic Therapy; Treatment Outcome; Aged, 80 and over; Time Factors; Registries; lidé středního věku; neuroimaging; senioři; Administration, Intravenous; intravenózní podání; Brain Ischemia; lidé; časové faktory; Stroke; Middle Aged; ischemie mozku; Fibrinolytic Agents; alteplase; Female; výsledek terapie; tkáňový aktivátor plazminogenu; senioři nad 80 let; registrace; Male; safety; ženské pohlaví; cerebrální krvácení; fibrinolytika; Humans; mužské pohlaví; Cerebral Hemorrhage; cévní mozková příhoda; trombolytická terapie; prognosis